BIBLIOMETRIC ANALYSIS OF SECTORAL SHIFTS AND INVESTOR BEHAVIOR - Judijanto, Loso (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study explores the dynamics of investor behavior, investments, and the influence of financial markets through a bibliometric analysis using VOSviewer. The keyword mapping reveals "Investor Behavior" as the central theme, interlinked with behavioral finance, decision-making, and emerging technologies. Key findings indicate the significance of financial literacy, the impact of global crises such as COVID-19, and the rising prominence of sustainability and ESG trends in shaping investment practices. Furthermore, advanced tools like artificial intelligence and machine learning are transforming financial markets. The study highlights the multidisciplinary nature of this field, emphasizing the role of psychology, technology, and economics in advancing the understanding of investor decision-making. Practical implications for financial institutions and advisors are also discussed to enhance investment strategies and decision-making frameworks.